Review of the interaction mechanism for droplets and foliage under sprinkler irrigation and water-fertilizer integration - Hu, Bin; Li, Hong; Jiang, Yue; Tang, Pan; Du, Longfei (International Journal of Agricultural and Biological Engineering, 2024)
With a focus on the global tension between water resources and energy, the use of water-fertilizer integration technology in sprinkler irrigation has seen a rise. However, achieving efficient and effective fertilizer application remains a significant challenge. This study delved into the interaction mechanism between droplets and foliage during sprinkler fertigation, as well as discusses the application of water-saving and energy-saving irrigation methods in agriculture to address water crises and propel agricultural modernization. This study highlights two main aspects of this issue, that is, the droplet and foliage impact process, and the droplet and foliage dynamic interaction including foliar interception, leaf absorption, and leaf burning. Major challenges, such as inefficiencies in foliar interception and uncertainties in fertilization, have been identified, calling for further investigation into these areas. Moreover, perspectives to promote fertilization technology are proposed, including research on the dynamic impact of fertigation droplets on foliage, the development of universal models for leaf fertilizer retention, and the determination of critical fertigation concentrations under varying conditions to prevent leaf burning. This comprehensive review aims to provide a theoretical basis for establishing an integrated fertigation system for sprinkler irrigation and foster innovation in water-fertilizer integration technology. Keywords: sprinkler irrigation, fertigation droplets, interaction mechanism, foliar process DOI: 10.25165/j.ijabe.20241705.8892 Citation: Hu B, Li H, Jiang Y, Tang P, Du L F. Review of the interaction mechanism for droplets and foliage under sprinkler irrigation and water-fertilizer integration. Int J Agric & Biol Eng, 2024; 17(5): 1-13.